Exploring the link between teacher-student interactions and EFL student motivation: Insights from Rwandan secondary schools - Ndayisenga, Jean d'Amour; Kuswandono, Paulus (Journal on English as a Foreign Language, 2025)
Many studies have reported that strong motivation between students and their teachers leads to successful English language learning. The vital function of teacher-student interactions in improving student learning still lacks comprehensive research in multilingual countries, particularly in the Rwandan EFL context. This research investigates how teacher-student relations affect the motivational levels of EFL students from Rwandan secondary schools, and how senior English teachers and students develop intrinsic and extrinsic motivation through emotional support, individualized teaching methods, and interactive respect. The study employed a qualitative method with a case study design. Data were gathered from ten teachers and four high school students using semi-structured interviews, and then analyzed thematically. The results indicate that good teacher-student relations promote English learning by motivating students' active participation and better results, which are ensured by the teacher's interest and positive attitude towards students. The research affirms the need for teacher professional development programs, which have the potential to impart practical, relational teaching strategies to various students. The result of studies assists in the acquisition of multicultural language learning. Policymakers can consider these findings to develop education policies promoting student motivation and EFL success in Rwandan classrooms.